Regional, demographic and temporal trends in anemia and malignant cancer-related mortality in U.S. older adults: a nationwide CDC WONDER analysis (1999–2020) - Khan, Muhammad Sarim Azad; Chaudhary, Asma; Khan, Mirha Imran; Ajaz, Ibrahiem Azeem; Khalid, Arham; Waheed, Aroosha; Amin, Mohammed Hammad Jaber (Frontiers in Oncology, 2026)
PurposeAnemia and malignancy concurrently contribute to reduced quality of life, treatment intolerance, and increased morbidity and mortality, disproportionately affecting older adults, socioeconomically disadvantaged groups, and minority populations. Despite its clinical importance, national patterns and population-level disparities in the mortality burden associated with this comorbidity remain poorly characterized. This study aims to examine mortality trends associated with concurrent anemia and malignancy in the United States using CDC WONDER (Centers for Disease Control and Prevention Wide-Ranging Online Data for Epidemiologic Research) database, with a focus on demographic and geographic disparities to inform targeted interventions.MethodsMortality data from CDC WONDER were analyzed for individuals aged 65 years and older using ICD-10 codes C00–C97 for malignancies and D50–D64 for anemia. Age-adjusted mortality rates (AAMRs) and annual percent changes (APCs) were calculated by year, age, sex, race/ethnicity, cancer type, and geographic region. Subgroup analyses focused on common anemia-associated cancers, including colorectal, gastric, lung, ovarian, female genital, breast, prostate, and hematologic malignancies, based on national prevalence.ResultsBetween 1999 and 2020, there were 264,331 anemia and malignancy -related deaths among U.S. adults aged ≥65. The overall AAMR remained relatively stable moving from 31.5 in 1999 to 31.1 in 2020. A significant decline occurred through 2017 (APC: –0.86), followed by a sharp increase from 2017 to 2020 (APC: 4.63). Males had higher AAMRs than females (28.8 vs. 22.6). Black individuals had the highest mortality (42.4). The Midwest had the highest regional AAMR (30.6), while the South had the lowest (27.6). States in the top 90th percentile for AAMR included North Dakota, Maryland, Rhode Island, West Virginia, and DC. Nonmetropolitan areas had higher AAMRs than metropolitan ones (32.9 vs. 27.8). Colorectal cancer showed the largest decline (AAPC: -2.03) followed by gastric (AAPC: -1.96) and prostate cancer (AAPC: -1.40), while breast, lung, gynecological, and hematological cancers remained stable.ConclusionAmong adults aged ≥65, anemia and malignancy-related mortality declined until 2017 but increased sharply through 2020, with highest rates in males, Black individuals, and nonmetropolitan/Midwestern residents. Declines were seen in colorectal, gastric, and prostate cancers, while other cancers remained stable, highlighting the need for targeted interventions to reduce disparities.